Power of space, space of power: the sociocultural complexities in the institutionalization of "Ezeship" in non-Igbo states in Nigeria (2012)
This article looks at the social and cultural complexities that the institutionalization of “ezeship” in non-Igbo states in Nigeria generated and the home-diaspora intersections of power that underlay, contended with, and intersected the sociocultural formation and that eventually contributed to its dissolution. It also investigates the implications of the current scenario on the coordination of disparate Igbo migrant groups in non-Igbo states in Nigeria on one hand and the Igbo sociocultural development on the other. Empirical evidence was employed to generate data for this study. Methods include observation, key informant interviews, and focus group discussions.